PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT TERHADAP PENCEGAHAN PENULARAN CACAR MONYET - Agil Putra Tri Kartika; Ito Wardin; Arya Sumantri (Ensiklopedia of Journal, 2025)
Abstract: Monkeypox (Mpox) is a disease caused by infection with the monkeypox virus. The monkeypox virus is in the same family of viruses as the variola virus, which is the virus that causes smallpox. The monkeypox virus has been found in small rodents, monkeys, and other mammals that live in the area. The incidence of monkeypox in Indonesia from 2022 to August 2024 was 88 cases. Public knowledge, attitudes, and behavior play an important role in preventing the transmission of monkeypox. The purpose of this research is determine level of knowledge, attitude and behavior of the community towards preventing the transmission of monkeypox in the Pulasaren Primary Health Center of Cirebon City in 2024. This research is a quantitative descriptive study involving 99 people in the Pulasaren Primary Health Center in Cirebon City using cluster random sampling. Data collection was conducted using a questionnaire. Data analysis used a percentage frequency distribution. This research shows that 47.5% of the community has a low level of knowledge, 51.5% have a positive attitude, and 58.6% exhibit good behavior towards the prevention of monkeypox transmission. Stakeholders need to provide accurate information to the community about monkeypox transmission prevention so that the community's knowledge, attitudes, and behaviors are not misguided.Keywords: Monkeypox, Knowledge, Attitude, Behavior.